Association between types of home healthcare and emergency house calls, hospitalization, and end‐of‐life care in Japan - Sun, Yu; Iwagami, Masao; Komiyama, Jun; Sugiyama, Takehiro; Inokuchi, Ryota; Sakata, Nobuo; Ito, Tomoko; Yoshie, Satoru; Matsui, Hiroki; Kume, Keitaro; Sanuki, Masaru; Kato, Genta; et al. (Journal of the American Geriatrics Society (JAGS), 2023)
Background To meet the increasing demand for home healthcare in Japan, as part of the national healthcare system, home care support clinics/hospitals (HCSCs) and enhanced HCSCs were introduced in 2006 and 2012 respectively. This study aimed to evaluate whether HCSCs has succeeded in providing 24‐h home care services through the end of life. Methods A retrospective cohort study was conducted using the national database in Japan. Participants were ≥ 65 years of age, had newly started regular home visits between July 2014 and September 2015, and used general clinics, conventional HCSCs, or enhanced HCSCs. Each patient was followed up for 6 months after the first visit. The outcome measures were (i) emergency house call(s), (ii) hospitalization(s), and (iii) end‐of‐life care defined as in‐home death. Multivariable logistic regression analyses were performed for statistical analysis. Results The analysis included 160,674 patients, including 13,477, 64,616, and 82,581 patients receiving regular home visits by general clinics, conventional HCSCs, and enhanced HCSCs respectively. Compared to general clinics, the use of conventional and enhanced HCSCs was associated with an increased likelihood of emergency house calls (adjusted odds ratio [aOR] and 95% confidence intervals [CIs] of 1.62 [1.56–1.69] and 1.86 [1.79–1.93], respectively) and a decreased likelihood of hospitalizations (aOR [95% CIs] of 0.86 [0.82–0.90] and 0.88 [0.84–0.92] respectively). Among 39,082 patients who died during the follow‐up period, conventional and enhanced HCSCs had more in‐home deaths (aOR [95% CIs] of 1.46 [1.33–1.59] and 1.60 [1.46–1.74], respectively) compared to general clinics. Conclusions HCSCs (especially enhanced HCSCs) provided more emergency house calls, reduced hospitalization, and enabled expected deaths at home, suggesting that further promotion of HCSCs (especially enhanced HSCSs) would be advantageous.